Estimation of Water Erosion and the Transportation of Sediments in the Upper Basin of Cuxtepeques River, Chiapas, Mexico (2020)
Changes in land use and increased intensity of rainfall are factors of greater influence that accelerate the soil erosion process. The application of basin scale sedimentological models integrated to Geographic Information Systems (GIS), is a tool that allows the definition of critical zones, and of this the establishment of measures of control of processes of production and transport of sediments. This study evaluates the water erosion using the Universal Soil Loss Equation (USLE), five scenarios were studied: corresponding to the start of operations of the El Portillo II (1980) dam, and the before and after the two extreme events in the basin (September 1998 and October 2005). The transport of sediments was evaluated by regression, using full annually records (eight years) of flows of two gauging stations in the basin. Overall, variations in erosion rates were observed with changes in the vegetal coverage and statistical homogeneity in the gauging data, which allowed adjust them to a regression model, with correlation coefficient upper to 88%.